The association between platelet transfusions and bleeding in critically ill patients with thrombocytopenia. Issue 1 (31st May 2017) - Arnold, Donald M.; Lauzier, Francois; Albert, Martin; Williamson, David; Li, Na; Zarychanski, Ryan; Doig, Chip; McIntyre, Lauralyn; Freitag, Andreas; Crowther, Mark; Saunders, Lois; Clarke, France; et al.
Abstract: Background: Platelet transfusions are commonly used to treat critically ill patients with thrombocytopenia. Whether platelet transfusions are associated with a reduction in the risk of major bleeding is unknown. Patients/Methods: Observational cohort study nested in a previous multicenter, randomized thromboprophylaxis trial in the intensive care unit (ICU). The objective was to evaluate the association between platelet transfusions and adjudicated major bleeding events. Platelet transfusion episodes were reviewed for timing of administration, product type, and dose. Major bleeding with and without platelet transfusions was adjusted for severity of thrombocytopenia, use of anti‐platelet agents, surgery and other covariates. Secondary outcomes were thrombosis, death in ICU and platelet count increment. Results: Among 2, 256 patients, 71 (3.1%) received 190 platelet transfusions. Of those, 121 (63.7%) were administered to 54 non‐bleeding, thrombocytopenic patients. Adjusted rates of major bleeding were not statistically different with or without the administration of platelet transfusions (hazard ratio for transfused patients 0.85; 95% confidence interval, 0.42‐1.72). We did not find a significant association between platelet transfusion use and thrombosis or death in ICU in adjusted analyses. Thrombocytopenia, anemia, major or minor bleeding and use of anticoagulants were associated with platelet transfusion administration. The median post‐transfusion platelet count increment was 20×10 9 /L at 3.5 hours post‐transfusion. Conclusions: Rates of major bleeding were not different for patients who did and did not receive platelet transfusions. Inferences were limited by the small number of transfused patients. Clinical trials are needed to better investigate the potential hemostatic benefit and potential harms of platelet transfusions for this high‐risk population.